The Asthma Control Questionnaire as a clinical trial endpoint: past experience and recommendations for future use. Issue 9 (15th July 2014) - Barnes, P. J.; Casale, T. B.; Dahl, R.; Pavord, I. D.; Wechsler, M. E.
Abstract The goal of asthma treatment is to control the disease according to guidelines issued by bodies such as the Global Initiative for Asthma. Effective control is dependent upon evaluation of symptoms, initiation of appropriate treatment and minimization of the progressive adverse effects of the disease and its therapies. Although individual outcome measures have been shown to correlate with asthma control, composite endpoints are preferred to enable more accurate and robust monitoring of the health of the individual patient. A number of validated instruments are utilized to capture these component endpoints; however, there is no consensus on the optimal instrument for use in clinical trials. The Asthma Control Questionnaire (ACQ) has been shown to be a valid, reliable instrument that allows accurate and reproducible assessment of asthma control that compares favourably with other commonly used instruments. This analysis provides a summary of the use of ACQ in phase II, III and IV asthma trials. Comparisons between the ACQ and other instruments are also presented. Our analysis suggests that the ACQ is a valid and robust measure for use as a primary or secondary endpoint in future clinical trials.